Hadis Al-Rada’ah Al-Kabir: Susuan bagi Orang Dewasa dalam Perspektif Hadis - Han, Muhamad Ibtissam; Ubaidillah, Asep (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2022)
This paper will explain how the concept of breastfeeding for adults in the perspective of hadith. Al-Rada'ah according to Syara, namely the process of sucking putting at around two years of age in small children has reached human milk in his stomach. However, there are two traditions narrated by Muslims and also Ibn Majah who explained that at one time the Messenger of Allah had ordered a woman to breastfeed an adult male. This happened because the woman had previously complained of a man going back and forth in and out of his house without restrictions and was worried something might happen. And the command of the Prophet was done so that the adult male becomes a mahram to the woman, namely mahram radla’ah. However, both traditions are considered to be in much contradiction with the propositions of the Qur'an and other traditions and the opinions of the majority of the scholars. Therefore this paper tries to trace the quality of the validity of the two traditions and to explore the opinions of the scholars on the matter. From these searches found a conclusion that in terms of sanad, the hadith continued to the Prophet. However, in terms of matan, these traditions contradict many verses of the Qur'an, other traditions and the opinions of the majority of the scholars even though there are also some scholars who argue that there is no problem with the sighting of the two traditions. But in the end the scholars believe that the hadith is true, but it is a tradition that is specific to the case that occurs in the traditions of the blissous or can be spelled out as relief given by the Messenger of Allah to that person and objection to others both those who lived during the time of the Prophet and those who live afterwards until now.